IDENTIFIKASI PERILAKU HARIAN BUNGLON SURAI (Bronchocela jubata Dumeril & Bibron, 1837) PADA SAYURAN ORGANIK KELURAHAN KARANGREJO METRO UTARA SEBAGAI SUMBER BELAJAR BIOLOGI - Widyo Andre Pramono; Widya Sartika Sulistiani; Suharno Zen (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2023)
The surai chameleon (Bronchocela jubata Dumeril & Bibron, 1837) is a carnivorous arboreal reptile. The temperature body is poikiloterm and has a roleas insect biocontrol in organic vegetable farming. The objectives of this study were 1) to determine the daily behavior of surai chameleon (Bronchocela jubataDumeril & Bibron, 1837) in organic vegetables in Karangrejo Village, North Metro. 2) to be used as a learning resource in the form of brochures for grade Xsenior high school students on ecosystem material. The brochures that discusses the daily behavior of animals as a biotic component. The research was conducted using the VES (Visual Encounter Survey) method. The research was conducted on fourteen-twenty December two thousand twenty. The time of observation was carried out in the morning at 06.00 a.m.-20.00 p.m (with two until three hour time intervals). Data were collected using the VES (Visual Encounter Survey) method and analyzed descriptively. The results showed that the behavior of the surai chameleon (Bronchocela jubata Dumeril&Bibron, 1837) in a day includes the behavior of eating insects, basking, resting, looking from side to side, jumping, hiding, sleeping and moving. The behavior of the surai chameleon(Bronchocela jubata Dumeril & Bibron, 1837) as a diurnal reptile is mostly done in the morning, afternoon and evening. The dominant behavior is the behavior ofresting and moving, while the behavior that is rarely done is the behavior of eating insects and the behavior of looking left and right. Utilization of researchresults used as a source of learning biology in the form of brochures for senior high school class X semester 2 ecosystem material.